Influence of Taxpayer's Knowledge and Tax Sanctions on Taxpayer Compliance with Awareness of Tax Payment as A Moderator - Afandi, Pandi; Abdurrosid, Edi Wicaksono; Sudarmawanti, Erna; Nurrahmawati, Dwi (Global Health Science Group, 2024)
The aim of the research is to empirically test the influence of taxpayer knowledge and tax sanctions on the payment compliance of individual taxpayers in Kudus Regency with taxpayer awareness as a moderator, with a sample size of 100 respondents who have submitted annual tax returns to KPP Pratama Kudus. The results of the research show that taxpayer knowledge has a significant effect on compliance with individual tax payments, but tax sanctions do not have a significant effect on compliance with individual tax payments in Kudus Regency. Taxpayer awareness has not succeeded in strengthening the influence and sanctions of taxes on compliance with individual tax payments in Kudus Regency. As much as 59.2 percent of knowledge, tax sanctions and taxpayer awareness contribute to compliance in paying individual taxes. Massive socialization to increase tax literacy supported by the tax digitalization program needs to continue to be encouraged in line with increasing service quality so as to increase mandatory confidence in fulfilling tax obligations and increasing the achievement of tax revenue targets. Taxpayer awareness in this research failed to strengthen the influence of knowledge and tax sanctions on compliance in paying taxes so that it is possible to modify it by including other variables such as tax avoidance, motivation, commitment to taxes or other variables.